Knowledge and Perception of Veterinary Students in Ghana on Telemedicine (Nigerian Journal of Physiological Sciences, 2021)
This study aimed at assessing the knowledge base and perception of telemedicine among veterinary students in Ghana.  It involved a cross sectional survey and online structured questionnaires were administered to 114 veterinary students to access their knowledge of telemedicine and the perceived utilisation, benefits, complexity and disadvantages of telemedicine. Descriptive statistics analysis was performed on the data collected using SPSS version 20 and Pearson Chi-square test was used to determine the significant association between categorical variables which were grouped. Statistical significance was tested at 5% significance level. The students exhibited good knowledge and perception of telemedicine with a mean response of 4.947 ± 1.374 and 3.473±1.115; represented by 86.8% and 78.9% of the students respectively. 92.1% had heard of the term ‘telemedicine’ from the internet and social media platforms. The level of study of veterinary students had a significant effect (p